Pengaruh Perilaku Keberagamaan Orang Tua Terhadap Motivasi Belajar PAI dan Ketaatan Beribadah - Wuki Nur Vika; Muhammad Haji Noh; Ahmad Mujib; Sarjuni Sarjuni (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
Students consider Islamic religious lessons to be unimportant and difficult so that their learning motivation is low. This type of research is quantitative research. The population in this study was class VII SMP N 5 Demak which amounted to 147 students. The sampling technique in this study used the slovin formula. The sampling technique used was random sampling. The sample in this study amounted to 99 people. Data analysis technique using r product moment. The results showed that  the calculation of r product moment, the value of rcount is 0.353. This means, the value of rxy 0.353 > r table 0.1646 then the first hypothesis is accepted. That is, there is an influence between the religious behavior of parents on the motivation to learn PAI in seventh grade students of SMP N 5 Demak. There is a positive and significant influence on the religious behavior of parents on students' obedience to worship. This can be seen from the results of the correlation calculation using r product moment, the value of rcount is 0.400. Based on the r value obtained, it is necessary to consult the product moment correlation coefficient in the table with N = 99 both at a significant level of 5%, a value of 0.1646 is obtained, and at a significant level of 1%, a value of 0.2312 is obtained. This means, the value of rxy 0.400 > r table 0.1646 then the second hypothesis is accepted.